Comparative study on stability of coconut oil, sunflower oil and palm oil during continuous deep frying - Sharanke, K.; Sivakanthan, S. (Ceylon Journal of Science, 2022)
This study was carried out to evaluate the stability of three oils, namely, coconut oil, sunflower oil and palm oil during continuous deep frying. An experiment was conducted by frying potato slices at 175±5°C for 15 minutes (one cycle) using different oils. The same oils were reused for frying over a period of 12 hours and samples were collected after every two hours of frying. The oil samples were tested for chemical and physical changes and oxidative stability during frying. Rates of increase in acid value, p-anisidine value and peroxide value were higher in sunflower oil (0.06 mg NaOH /g oil/hour, 8.03/hour and 0.13 meq/kg/hour, respectively) than in other oils. Smoke points of all oils decreased significantly over time, with the highest reduction in palm oil (208.5 to 172 ºC). Total polar compounds increased significantly during frying in all samples. Major reductions were observed in the linoleic acid content in palm oil and sunflower oil. Trans fat content did not increase significantly in coconut oil, whereas, a slight increase was observed in palm oil (1.14 to 1.21%) and sunflower oil (0.61 to 0.72%). In conclusion, coconut oil showed the highest stability whereas sunflower oil showed the lowest stability during continuous deep frying.
Keywords: Continuous deep frying; Frying cycle; Oxidative stability; Total polar compounds; Trans fat